Vegetation composition, soil properties, and carbon stock of montane forests along a disturbance in the Garhwal Himalaya, India - Tiwari, Avadhesh; Khanduri, Vinod Prasad; Rawat, Deepa; Singh, Bhupendra; Riyal, Manoj Kumar; Mishra, Gaurav; Kumar, Munesh (Frontiers in Forests and Global Change, 2023)
The management of forests is essential for the conservation of biodiversity and climate change. Studies on the variation in forest tree diversity and carbon sequestration by the forests along altitudinal gradients are limited for most parts of the Garhwal Himalaya. The present study was carried out in montane forests in a part of district Tehri of the Garhwal Himalaya, India at four different sites between altitudinal ranges of 850 to 2,200 masl (i.e., 850–1,500 masl under sub-tropical region and 1,800–2,200 masl under temperate region) for vegetation, soil, and carbon stock analysis using different parameters including the existing pressure on the sites for fuel, fodder, timber, grazing, and browsing. All the standard methods were used for vegetation and soil analysis. The highest value of tree diversity (H = 0.48) and concentration of dominance (CD = 0.95) was recorded at 850–1,100 masl altitude under sub-tropical forests. The aboveground biomass density (AGBD) and belowground biomass density (BGBD) ranged from 271 to 703.20 and 83.21 to 163.92 Mg ha–1, respectively. The pH value ranged from 5.63 to 6.86 (0–15 cm) and 6.17 to 7.21 (15–30 cm). Similarly, soil organic carbon (SOC) was reported to range from 1.86 to 2.57% and 1.78 to 2.44% at 0–15 cm and 15–30 cm depths, respectively. Available nitrogen (N) under temperate forests was reported to be significantly higher than at other altitudes. Among the studied parameters, a significant positive correlation was reported between the pH of the soil and the Shannon–Wiener and Margalef diversity indices. The study revealed that the sub-tropical region was more diversified in terms of tree species whereas soil properties were reported to be better in the temperate region. Among the species in the study region, Pinus roxburghii, Boswellia serrata, Quercus leucotrichophora, and Cedrus deodara have shown good potential for carbon storage. Thus, based on the dominant and associated species present in the area, forest management activities may be followed for the survival and regeneration of species with the potential of being the next dominant species in the future.